Deep Vein Thrombosis While Still on NOAC - Barakoti, Murari Prasad (Journal of National Heart and Lung Society Nepal, 2024)
Novel oral anticoagulation treatment has been extensively used for thromboprophylaxis in atrial fibrillation and other clinical conditions because of predicable pharmacokinetic profile and safety. However, rarely plasma drug level variation can occur that can lead to thrombotic and bleeding events. We describe a case of deep vein thrombosis in a compliant patient still on apixaban. Anticoagulation failure with NOAC is concerning and obviously there is growing need of assay in these subsets showing the activity of NOAC. Till the availability of such methods, switching back to conventional therapy with Vitamin K antagonist with accurate monitoring could be appropriate strategy.